¡Volved a Rumanía, por favor! la política de retorno del gobierno rumano y sus implicaciones en los inmigrantes que se encuentran en España - Mercedes Gordo Márquez (Cuadernos de Geografía de la Universitat de València)
The international emigration Romanian has meant the loss of a great number of workforce that now, in a phase of important growth of the country, makes itself felt so important. To face this situation the Government of Romania has started a program of voluntary return. This article offers a reflection on the same one and its concretion with respect to immigrants of this country who are in Spain. Analyzes its viability and the effects that is taking. It also approaches the implications it can have on remittances and the contradictions arising from the campaign that also is stimulated to improve the image of their compatriots in Spain.